What Are Public Libraries For? Culture As a Determinant of Conceptualizations of Public Library Services for Forced Migrants. Issue 1 (14th October 2022) - Salzano, Rachel; Brazier, David; Hall, Hazel; Webster, Gemma
ABSTRACT: Public libraries offer important services for newcomer populations, including forced migrants. They help facilitate the integration of forced migrants into the host country, increase their levels of trust within new communities, and build social capital. To date, however, the determinants of forced migrant engagement with public library services has been left unexplored. Here the impact of culture on conceptualizations of public library services, and the role of this on the adoption and use of public library services, is investigated using the Theory of information worlds . The analysis is based on data collected in semi‐structured interviews with 30 UK service gatekeepers for forced migrants. Thematic analysis identified three conceptualizations of public library services as: (1) leisure services, that (2) offer information services, (3) as part of a larger system that includes other functions such as immigration and policing. These conceptualizations impact service use and, importantly, non‐use. Further contributions of the work include the proposal that Maslow's (1943) Hierarchy of needs may serve as a moderating variable for the five societal elements of the Theory of information worlds, and practical recommendations for public library staff keen to increase forced migrant engagement with the services that they offer.